The Role of Executive and Legislative Institutions in Sharia Implementing in Aceh - Zulfahmi Zulfahmi (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2019)
The Role of Executive and Legislative Institutions in Sharia Implementing  in Aceh